2021
DOI: 10.3390/jpm11111218
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Lifestyle Behaviors and Quality of Life Differ Based on Multiple Sclerosis Phenotype

Abstract: Multiple sclerosis (MS), a neuroinflammatory disorder, occurs as non-progressive or progressive phenotypes; both forms present with diverse symptoms that may reduce quality of life (QoL). Adherence to healthy lifestyle behaviors has been associated with higher QoL in people with MS; whether these associations differ based on MS phenotype is unknown. Cross-sectional self-reported observational data from 1108 iConquerMS participants were analysed. Associations between lifestyle behaviors and QoL were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The strengths of our study include primarily the large international population of pwMS, with clinical and demographic characteristics aligned with pwMS reported in other studies [27,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of our study include primarily the large international population of pwMS, with clinical and demographic characteristics aligned with pwMS reported in other studies [27,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies across these studies and our findings may be attributable to the challenges of collecting self-reported diet data, resulting in potential bias and measurement error [25], and changes to diet over the study period not being captured. Others have reported low-fat and anti-inflammatory diets as being potentially beneficial to QoL in pwMS, although the benefits may not be sustained beyond 12 months [26][27][28][29]. Previous clinical trials have reported mixed associations between omega-3 supplementation and QoL [30], possibly due to different dose and form, as well as different tools for measuring QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the sample is made up mostly of patients who present the relapsing remitting phenotype (83.6%) and to a lesser extent by patients with progressive clinical forms (16.3%). It is well known that both RRMS and progressive MS present important differences in the severity of physiological, psychological, and motor symptoms; which impacts in different ways on the quality of life of these patients (Nag et al, 2021). In future studies it is also important to control for the effect of covariates such as depression, anxiety, EDSS and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for patients with progressive disease courses for whom drug therapies are limited and who are often more frequently and profoundly affected given advanced disease stages and greater severity of symptoms, i.a. cognitive deficits [3][4][5]. This can lead to low perceived self-efficacy within the context of the disease, which in turn can result in a low level of coping skills and self-management [6].…”
Section: Introductionmentioning
confidence: 99%